Enterprise Architecture and Business Requirement Modeling Using the Zachman Framework - Ukie Tukinah; Fajriani Azis; Soussou Raharimalala (Global Research and Collaboration, 2025)
Zachman frameworks are frameworks created to get enterprise-wide architectures. Zachman's framework is simple, and logical in nature that can help manage the information infrastructure of an enterprise. Although simple, Zachman frameworks can help align IT and business needs. PT. Bhakti Karya Cemerlang is a business that offers staff outsourcing services. Cleaning services, production operators, secretaries, clerical employees, sales promotion girls, maintenance workers, drivers and receptionists are some of the outsourcing services provided. Until July 2017, PT. Bhakti Karya Cemerlang has a total of 700 employees. Based on the requirements of partner companies, PT. Bhakti Karya Cemerlang places people. Therefore, the number of employees assigned to each partner company is unique. Office for PT. Bhakti Karya Cemerlang can be found in Tangerang and Karawang. This section is supported by a literature review that serves as a support for the research concept. Authors must provide a review of primary and recent literature (references to journal articles and conference proceedings). Research is not limited to theory, but is based on empirical evidence. Enrich this introductory section through the efforts of other stakeholders.